Detection, discrimination and absolute quantitation of Tomato spotted wilt virus isolates using real time RT-PCR with TaqMan (R) MGB probes - Debreczeni, Diana E.; Ruiz-Ruiz, Susana; Aramburu, Jose; Lopez, Carmelo; Belliure, Belén; Galipienso, Luis; Soler, Salvador; Rubio, Luis (2017)
A quantitative real-time reverse transcription-polymerase chain reaction (RT-qPCR) procedure using a general primer set and three TaqMan (R) MGB probes was developed for general and genotype-specific detection and quantitation of the genomic M segment of Tomato spotted wilt virus (TSWV). Standard curves using RNA transcripts homologous to the three probes allowed reproducible quantitative assays with a wide dynamic range (10(3)-10(10) TSWV M segment RNA copies/ng of total RNA) and high sensitivity. This protocol was assayed with a battery of TSWV isolates, covering the range of the present known genetic variation, in single and/or mix infections in three plant hosts, as well as in the thrips vector Frankliniella occidenialis. This quantitative detection assay will be a valuable tool for molecular biology and epidemiology studies, diagnosis and disease control.